Temporal stability of the Czech translation of the Satisfaction with Life Scale: test-retest data over one week - Navrátil, Marek; Lewis, Christopher Alan (Psychological reports, 2006)
The present study supplemented the limited 1999 psychometric data by Lewis, et al. on the Czech translation of the Satisfaction With Life Scale by examining the temporal stability of the measure over a 1-wk. period for 64 Czech undergraduate university students. Analysis indicated stability across the two administrations was very high (r=.90), and there was no significant change between Time 1 (M=23.7, SD=5.1) and Time 2 (M=24.1, SD=5.5). Short-term test-retest reliability of this Czech translation is supported.
Keywords: dospělí; Czechoslovakia; Humans; Československo; překlady; reprodukovatelnost výsledků; Time Factors; Translations; mužské pohlaví; Personal Satisfaction; Adult; Language; osobní uspokojení; časové faktory; jazyk (prostředek komunikace); ženské pohlaví; lidé; Reproducibility of Results; Quality of Life; Male; kvalita života; Female